PENILAIAN KONDISI JEMBATAN MENGGUNAKAN BRIDGE MANAGEMENT SYSTEM (BMS) DAN BRIDGE CONDITION RATING (BCR) - Wilhman Harywijaya; Mochammad Afifuddin; Muhammad Isya (Prodi Magister Teknik Sipil Unsyiah, 2020)
The bridge assessment and checking is an effort to gain well performance and vouch for the decline condition of the bridge to ensure the bridges could be restored back under its stability based on its performance. The aim of this study is to check the bridge damaged by inspecting the condition value and damage code in the field by using BMS and Bridge Condition Rating (BCR) in order to obtain the accuracy in bridge maintenance. This research was conducted on 4 Bridges on the road Kr. Raya-BTS. Banda Aceh and Lambaro-BTS. Pidie, those are Kr. Angan bridge (STA. 013 + 400), Kr. Inong bridge (STA. 040 + 600), Kr. Geunapet A bridge (STA. 063 + 700), and Kr. Geunapet B bridge (STA. 063 + 700). Based on the BMS method, the writer found that Kr. Angan bridge was in 0 condition value, the condition value for Kr. Inong bridge was 2, the condition value for Kr. Geunapet A bridge was 0 and Kr. Geunapet B bridge was 0. Based on the results by using the BCR method, it can be seen that the condition value was 5,36 for Kr. Angan bridge, 5,52 for Kr. Inong bridge, 5,28 for the Kr. Geunapet A and 5,28 for Kr. Geunapet B. In the method of BMS the assessment of the condition of the bridge from good to bad starts from a small to large values namely from 0 to 5, while in the method of crack the assessment of conditions starting from bad to good is 7 to 1. Furthermore, referring to the BMS and BCR comparison, it could be concluded that both BMS and BCR needed the same proposed treatment in the form of regular and periodic maintenance. While in the BCR method there was no assessment to handle floor drainage systems, backrests, and safety building.